2015
DOI: 10.1098/rstb.2014.0100
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle growth and surface chemistry changes in cell-conditioned culture medium

Abstract: When biomolecules attach to engineered nanoparticle (ENP) surfaces, they confer the particles with a new biological identity. Physical format may also radically alter, changing ENP stability and agglomeration state within seconds. In order to measure which biomolecules are associated with early ENP growth, we studied ENPs in conditioned medium from A549 cell culture, using dynamic light scattering (DLS) and linear trap quadrupole electron transfer dissociation mass spectrometry. Two types of 100 nm polystyrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Agglomerate’s size distribution was a function of the sample’s chemical signature (Fig. 3), with cell culture media with 5% serum containing appropriate cell growth proteins favoring larger agglomerates formation than PBS alone, likely due to the interactions of the clays with the proteins in the media forming coronas [59,60]. Interestingly, analyses showed that CC displayed smaller diameter sizes in both media and PBS relative to the other three samples, likely due to the presence of the organic modifier (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Agglomerate’s size distribution was a function of the sample’s chemical signature (Fig. 3), with cell culture media with 5% serum containing appropriate cell growth proteins favoring larger agglomerates formation than PBS alone, likely due to the interactions of the clays with the proteins in the media forming coronas [59,60]. Interestingly, analyses showed that CC displayed smaller diameter sizes in both media and PBS relative to the other three samples, likely due to the presence of the organic modifier (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These media constituents can greatly affect the surface chemistry of MO-NPs by changing zeta potential, dissolving the particle, or blocking interactions. Media contents can make NPs unstable through ion/molecule/protein adsorption or loss of surface functionality, resulting in the formation of aggregates(36, 62). The role of complex NP corona ( i.e.…”
Section: Role Of Surrounding Media/microenvironment On Np Efficacymentioning
confidence: 99%
“…This knowledge gap partially results from the fact that NPs physicochemical properties, particularly its reduced size, hinder the application of traditional toxicity assays and further contribute to the misinterpretation of results and ambiguous conclusions among research groups (Dobrovolskaia et al, 2009). Additionally, the mandatory use of biological medium during toxicological assays can modify the NPs characteristics such as size, surface charge and morphology, through phenomenon's like protein corona formation and particle agglomeration, which will therefore influence the immunotoxicity profile of the NPs (Kendall et al, 2014). Therefore, a detailed characterization of the NPs in the experimental assay conditions is crucial to discuss the results, but is commonly absent from the scientific published reports.…”
Section: Introductionmentioning
confidence: 99%